STRATEGY MARKETING OF SHARIA BANKS OF MICRO SHARIA WAKAF IN INCREASING THE NUMBER OF CUSTOMERS (Case Study: Typical Islamic Micro Waqf Bank Kempek Cirebon) - Asih Widyanti (Journal of Social Science, 2020)
This study aims to find out how the implementation ofmarketing at the Sharia Micro Typical Sharia Bank KempekCirebon and marketing strategies used by the Micro WaqfBank in increasing the number of corporate customers. Theresearch method used is a qualitative method. The marketingstrategy used by the Typical Sharia Micro Waqf Bank inKempek Cirebon is to use segmenting, targeting andpositioning. Applying the characteristics of sharia marketingin the form of God, realistic, moral and humanistic. Marketsegments determined by the Micro Islamic Waqf Bank aregeographical segments, demographic segments,psychographic segments, and behavioral segments.Customers at the Micro Islamic Waqf Bank each year haveincreased, which of course this institution continues toincrease turnover. Customers are very interested in theproducts owned by this institution because they have very lowmargins. Islamic Micro Waqf Bank has done a goodmarketing implementation, even has a marketing strategy.The name of the Micro-Islamic Waqf Bank is already greatbecause it carries the name Pondok Pesantren TypicalKempek.Keywords: Marketing Strategy, Micro Islamic Waqf Bank,Customers.